Inference on the Possible Causes of Segregation Distortion from Open Pollination Progenies of Merkus Pine (Pinus merkusii) - ISKANDAR ZULKARNAEN SIREGAR; TEDI YUNANTO (HAYATI Journal of Biosciences, 2008)
Methods of analysis to infer the possible causes of segregation distortion were carried out using single tree progenies of Pinus merkusii. Tests on the progenies of the seed trees showing significant segregation distortion were performed at six gene loci, i.e. GOT-C, GOT-D, PGM-B, SKDH-A, NDH-A, and FDH-A. Results indicated that most fertilisation combination between female and male gametes occurred randomly. This study revealed that 11 out of 17 cases of distortion were detected in both gametes, while the other six were detected only in female gamet. The primary sources of such segregation distortions are discussed regarding to linkage relationships system of mating and post-zygotic viability selection. Key words: Pinus merkusii, segregation distortion, system of mating, viability selection